2023
DOI: 10.3390/ani13071236
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Expression Pattern and Functional Role of miR-10b in Intestinal Inflammation

Abstract: Implications of miRNAs for animal health management in livestock remain elusive. To identify suitable miRNAs as monitoring biomarkers, piglets were randomly selected for sampling on days 0, 1, 3, 7, and 14 post-weaning. The results show that miR-10b levels in the villus upper cells of the jejunum on days 3 and 7 were significantly lower than that on day 14 post-weaning and reduced by approximately 30% on day 3 and 55% on day 7 compared to day 0. In contrast, miR-10b in crypt cells decreased by approximately 82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…Moreover, the study found that miR-10b deficiency exacerbated the immune response, including infiltration of macrophages and Ly6G þ neutrophils in colon tissue, elevated serum levels of LPS, DAO, D-LA, TNF-α, IL-1β, IFN-γ, IgM, IgA, and IgG in mir-10b KO mice after DSS treatment. 54 We confirmed the elevated TNF-α expression in mir-10b KO mice compared to WT. These findings, together with our study, suggest that miR-10b deficiency leads to intestinal permeability, dysregulation of tight junctions, and gut immune dysfunction.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Moreover, the study found that miR-10b deficiency exacerbated the immune response, including infiltration of macrophages and Ly6G þ neutrophils in colon tissue, elevated serum levels of LPS, DAO, D-LA, TNF-α, IL-1β, IFN-γ, IgM, IgA, and IgG in mir-10b KO mice after DSS treatment. 54 We confirmed the elevated TNF-α expression in mir-10b KO mice compared to WT. These findings, together with our study, suggest that miR-10b deficiency leads to intestinal permeability, dysregulation of tight junctions, and gut immune dysfunction.…”
Section: Discussionsupporting
confidence: 71%
“…A recent study demonstrated that deficiency of miR-10b increased susceptibility to DSS-induced colitis. 54 This study also revealed increased intestinal permeability in mir-10b KO mice after DSS treatment.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In contrast, miR-199a-3p was down-regulated in both jejunal villus cells and crypt cells on day 7 after weaning. These findings were consistent with our previous report, which demonstrated that miR-10b, another member of the miRNA family, had a decreased expression after weaning [24]. Moreover, both miR-199a-5p and miR-199a-3p were found to be differently expressed along the villus-crypt axis, which agreed with a previous study demonstrating that miR-199a-5p and -3p were up-regulated in jejunal villus cells as compared with crypt epithelial cells [21].…”
Section: Discussionsupporting
confidence: 94%
“…Gene Ontology (GO) analysis was performed using Goatools with Bonferroni-corrected p < 0.05. Kyoto Encyclopedia of Genes and Genomes (KEGG) and Reactome were carried out by Metascape (v3.5.20230501) (https://metascape.org/, accessed on 3 May 2023) as previously described [24]. Prediction of target genes of miR-199a-5p or -3p was performed by StarBase v2.0 (https://starbase.sysu.edu.cn, accessed on 1 May 2023).…”
Section: Bioinformatics Analysismentioning
confidence: 99%